ANALISIS PERMASALAHAN PENERAPAN PENCEGAHAN DAN PENGENDALIAN INFEKSI (PPI) PADA PERAWAT DI RUMAH SAKIT XXX - Astrid Ribut Prihatiningtiyas Sudarwati (Rena Cipta Mandiri, 2026)
Hospitals are healthcare facilities that are at risk of healthcare-related infections. One of the most effective infection prevention efforts is the implementation of hand hygiene by healthcare workers. However, in its implementation, hand hygiene compliance is still often found to be suboptimal. This study aims to analyze the problem of hand hygiene compliance and efforts to improve compliance using the Lean Management approach, the USG method, and the PDSA cycle at XXX Hospital. This study used a descriptive qualitative method with an observational approach conducted during the internship. The data used were monitoring data on hand hygiene compliance of healthcare workers from October to December. The results showed that the level of hand hygiene compliance in October was 76.5%, in November 75%, and in December 79.1%. The results of the Lean Management analysis showed waste in the form of defects and motion that affected the implementation of hand hygiene. Based on the USG method analysis, the problem of suboptimal hand hygiene compliance is a priority problem that needs to be addressed. Improvement efforts are carried out through the PDSA method by increasing education, regular compliance monitoring, and providing adequate hand hygiene facilities. These efforts are expected to improve healthcare workers' compliance in implementing hand hygiene, thereby supporting the Infection Prevention and Control program in hospitals.